Developments in surface contamination and cleaning. Volume three, - Kohli, Rajiv; Mittal, Kashmiri L. (William Andrew, 2011)
The contributions in this volume cover methods for removal of particle contaminants on surfaces. Several of these methods are well established and have been employed in industrial applications for a long time. However, the ever- higher demand for removal of smaller particles on newer substrate materials is driving continuous development of the established cleaning methods and alternative innovative methods for particle removal. This book provides information on the latest developments in this topic area. The purpose of the Developments in Surface Contamination and Cleaning series is to provide.
Keywords: Surfaces (Technology); Surface contamination -- Prevention.; Particles -- Measurement.; Cleaning.; Coatings.; Dust control.; elektronické knihy; electronic books